2017
DOI: 10.1002/dc.23674
|View full text |Cite
|
Sign up to set email alerts
|

The significance of parakeratosis alone in cervicovaginal cytology of turkish women

Abstract: Our results demonstrate that a finding of parakeratosis on an otherwise negative Pap smear supports a follow-up HPV DNA test. Also we should consider whether the presence of parakeratosis should be included in standard cytology reports. Additionally parakeratosis trended toward increased frequency of HSIL in follow-up biopsy specimens. But it did not reach statistical significance. That is why larger studies are necessary to evaluate the association of parakeratosis and HSIL in colposcopic biopsy specimens. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although cytological studies of postmenopausal women are extremely limited, Halford et al 13 conducted a retrospective study of the correlation between histological outcomes and cervicovaginal cytological morphology in women 50 years and older, and they reported that both low- and high-grade histological lesions were associated with a cytological background displaying the predominance of mature intermediate and superficial squamous cells compared to the findings in negative women. Concerning the relationship between PK and dysplasia, Kir et al 12 reported that the prevalence of HPV positivity in women with PK was higher than that in women without PK. They also reported that HSIL was more frequently observed in HPV-positive women with PK than in those without PK, however, a statistical correlation was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cytological studies of postmenopausal women are extremely limited, Halford et al 13 conducted a retrospective study of the correlation between histological outcomes and cervicovaginal cytological morphology in women 50 years and older, and they reported that both low- and high-grade histological lesions were associated with a cytological background displaying the predominance of mature intermediate and superficial squamous cells compared to the findings in negative women. Concerning the relationship between PK and dysplasia, Kir et al 12 reported that the prevalence of HPV positivity in women with PK was higher than that in women without PK. They also reported that HSIL was more frequently observed in HPV-positive women with PK than in those without PK, however, a statistical correlation was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Parakeratosis (PK) is one of HPV infection related findings such as koilocytosis, dyskeratosis, nuclear hyperchromasia, multinucleation, and keratohyalin granules 11 . Although PK is associated with HPV infection, 12 its pathological significance in postmenopausal women is unclear. Similarly as cervicovaginal dysplastic lesions, HPV infects the squamous epithelium and induces keratinization, squamous differentiation, or dysplasia, which leads to squamous intraepithelial lesions (SIL).…”
mentioning
confidence: 99%
“…Hyperkeratosis and parakeratosis are defense responses of the chronically exposed epithelium to irritating or infectious events, including HPV infection. The literature diverges regarding an association of these findings with high-grade intraepithelial lesions, but studies have demonstrated a significant association with low-grade lesions and cytopathic HPV effects [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Hyperkeratosis was defined as keratotic cellular changes with mature anucleated cells and orangeophilic cytoplasm [19]. Parakeratosis was defined as small, keratinized squamous cells, densely orangeophilic, but with small pyknotic nuclei [20]. Giant cells were defined as cells with enlarged nuclei and macrocytosis with a concentric perinuclear halo, which may present bi/multinucleation [21].…”
Section: Methodsmentioning
confidence: 99%
“…During the epidemiological and diagnostic study of precancerous cervical lesions carried out in the region of Sidi Bel Abbes (north-western Algeria), dyskeratosis was identified in 8% of high-grade intraepithelial neoplasms [76]. Evaluation of dyskeratosis on cervicovaginal swabs in Turkish women shows that it is much more associated with a histological diagnosis of high grade intraepithelial neoplasia (p=0.8) [77]. In a study investigating factors associated with cervico-uterine changes in women from the city of Saint Catherine in western Brazil, dyskeratotic and binucleate cells were identified in 11.8% of intraepithelial neoplasias of the cervix.…”
Section: Cytological Alterations Predictive Of Papillomavirus Infectionmentioning
confidence: 99%